Preparation method of polymer adhesive capable of broad-spectrum adhesion based on hydrogen bond-containing amphiphilic deep-eutectic solvent of acrylic acid derivative

By constructing a dynamic multi-level network structure using an amphiphilic eutectic solvent containing hydrogen bonds based on acrylic acid derivatives, the problems of weak adhesion of existing adhesives on low surface energy materials and performance degradation in aqueous environments are solved. This achieves broad-spectrum strong adhesion and efficient VOCs adsorption to both hydrophilic and hydrophobic materials, and possesses reversible debonding capability and long-term stability.

CN121379440APending Publication Date: 2026-01-23HEBEI UNIV OF SCI & TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511878393.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-12
Publication Date
2026-01-23

AI Technical Summary

Technical Problem

Existing adhesives have weak adhesion to low surface energy materials, their performance degrades in water environments, and their VOCs adsorption capacity is insufficient, making it difficult to achieve broad-spectrum strong adhesion and reversible debonding to both hydrophilic and hydrophobic materials.

Method used

Using an amphiphilic eutectic solvent with hydrogen bonds based on acrylic acid derivatives, a dynamic multi-level network structure is constructed. By combining it with a chemical crosslinking agent to form an interpenetrating network, the hydrophobic and hydrophilic water regions are interwoven, and abundant hydrogen bond sites and micropores are introduced to enhance adhesion and VOCs adsorption capacity.

Benefits of technology

It maintains excellent interfacial stability and functional durability in underwater and complex chemical environments, achieves universal strong adhesion to different surface energy substrates, and has efficient VOCs adsorption capacity and recyclability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121379440A_ABST
    Figure CN121379440A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a polymer adhesive capable of broad-spectrum adhesion based on a hydrogen bond-containing amphiphilic deep eutectic solvent of an acrylic acid derivative, and belongs to the technical field of polymer adhesives. The preparation method of the adhesive comprises the following steps: S1, mixing a hydrogen bond donor and a hydrogen bond acceptor, heating and stirring until the mixture is clarified to obtain a eutectic solvent; s2, adding an acrylate monomer and an acrylamide monomer into the eutectic solvent, and uniformly mixing to obtain a mixture; and S3, sequentially adding a chemical cross-linking agent and a photoinitiator into the mixture, and carrying out photo-initiation to obtain the adhesive. The adhesive prepared by the invention has the characteristics of high adhesive power, debonding as required, excellent waterproofness, efficient VOCs adsorption, adaptability to hydrophilic and hydrophobic materials and the like.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of polymer adhesives, and more particularly relates to a preparation method of a hydrogen bond-containing amphiphilic eutectic solvent-based polymer adhesive with broad-spectrum adhesion based on an acrylic derivative. BACKGROUND

[0002] Adhesives are widely used because they can achieve convenient and low-damage substrate connection. Traditional thermosetting adhesives form irreversible covalent bonds through liquid-solid transition, and have high bonding strength, but also have obvious limitations: it is difficult to achieve on-demand debonding, and after curing, it is brittle and prone to breakage. In recent years, polymer adhesives as a class of quasi-solid elastic materials have received more and more attention. They maintain bonding stability by dissipating mechanical energy, and adapt to rough surfaces by virtue of soft material properties, rely on reversible physical interaction mechanisms such as hydrogen bonds, static electricity, π-π, ion-dipole, dipole-dipole, cation-π, and hydrophobic interactions to achieve adhesion to a variety of substrates. However, this type of adhesive, although it performs well on high-surface-energy materials such as glass and metal, is difficult to reliably adhere to inert low-surface-energy substrates such as polytetrafluoroethylene. This type of substrate is resistant to wetting and has few functional groups, making it difficult to form effective interfacial interactions. In addition, in a water environment, due to the hydrophilic nature of hydrogen bonds, surface hydration, polymer network instability, and ion diffusion, the adhesion strength often decreases significantly or even completely fails. At the same time, with the acceleration of industrialization, the emission of volatile organic compounds (VOCs) has become a serious environmental problem. VOCs not only pollute the atmospheric environment, but also have many adverse effects on human health, such as causing respiratory diseases, headaches, nausea, and other symptoms. The gel adhesives in the prior art still have deficiencies in VOCs adsorption capacity and cannot meet the requirements of efficient adsorption.

[0003] To address the above challenges, amphiphilic polymer networks have been proposed as a viable strategy to achieve broad-spectrum strong adhesion to hydrophilic / hydrophobic materials and to be suitable for underwater and high-humidity environments. The hydrophobic component in this type of polymer can inhibit water molecule penetration, maintain interfacial stability, and adhere to low-surface-energy materials such as PTFE through hydrophobic interactions; the hydrophilic component can form hydrogen bonds with the surface of materials such as glass, metal, and wood, thereby providing good adhesion to high-surface-energy materials. However, there are still very few polymer adhesives that can simultaneously exhibit high adhesion strength to both hydrophilic and hydrophobic materials, have underwater stability and on-demand debonding ability, and efficiently adsorb VOCs. Therefore, developing new environmentally friendly polymer adhesives with excellent comprehensive performance, strong environmental adaptability, convenient reversible operation, and VOCs adsorption is still an important and challenging task in the current material field. This not only solves the performance shortcomings of traditional adhesives, but also has profound theoretical and practical significance; at the same time, it also meets the strategic development direction of our country's innovation in key basic materials in the field of new materials and high-end manufacturing. SUMMARY

[0004] The purpose of the present application is to provide a preparation method of a polymer adhesive based on an amphiphilic deep eutectic solvent, which has high adhesion, can be debonded on demand, has excellent waterproofness, efficiently absorbs VOCs, and is suitable for a wide range of adhesion to hydrophilic and hydrophobic materials, to solve the problems of the prior art.

[0005] To achieve the above purpose, the present application provides the following solutions: One of the technical solutions of the present application: a preparation method of a polymer adhesive based on an amphiphilic deep eutectic solvent containing hydrogen bonds, which can be widely adhered, comprises the following steps: S1, mixing a hydrogen bond donor and a hydrogen bond acceptor, heating and stirring until clear to obtain a deep eutectic solvent; S2, adding an acrylic ester monomer and an acrylamide monomer to the deep eutectic solvent and mixing uniformly to obtain a mixture; S3, sequentially adding a chemical crosslinking agent and a photoinitiator to the mixture, and performing photo initiation to obtain the polymer adhesive.

[0006] Preferably, the hydrogen bond donor comprises triethyl phosphate, tributyl phosphate, menthol, thymol, thymol, borneol, n-butanol, n-hexanol, hydroxyphenyl ethyl ester, ibuprofen, p-hydroxybenzoic acid, or camphor; the hydrogen bond acceptor comprises tetrabutylammonium bromide, tetrabutylammonium chloride, tetrabutylammonium hexafluorophosphate, n-butyric acid, n-valeric acid, n-hexanoic acid, n-heptanoic acid, n-octanoic acid, decanoic acid, or lauric acid; the molar ratio of the hydrogen bond donor and the hydrogen bond acceptor is 4:1 to 1:4.

[0007] Preferably, the heating temperature is 50-120℃.

[0008] Preferably, the acrylic ester monomer comprises methyl acrylate, ethyl acrylate, butyl acrylate, 2-hydroxyethyl methacrylate, benzyl acrylate, isobornyl acrylate, 4-hydroxybutyl acrylate, 2,2,3,4,4,4-hexafluorobutyl acrylate, 2,2,2-trifluoroethyl acrylate, trifluoroethyl methacrylate, or tert-butyl acrylate.

[0009] Preferably, the acrylamide monomer comprises acrylamide, N-isopropyl acrylamide, N-hydroxyethyl acrylamide, N-hydroxymethyl acrylamide, 2-acrylamido-2-methylpropanesulfonic acid, or methacrylamide.

[0010] Preferably, the chemical crosslinking agent comprises N,N-methylenebisacrylamide, divinylbenzene or polyethylene glycol (diol) diacrylate; the photoinitiator comprises 2-hydroxy-2-methyl-1-phenylpropanone, 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone, benzoin dimethyl ether or 2,4-dihydroxybenzophenone.

[0011] Preferably, the mass ratio of the eutectic solvent, the acrylate monomer, the acrylamide monomer, the chemical crosslinking agent and the photoinitiator is (300-600):(300-800):(600-1600):(2-10):(10-30).

[0012] Preferably, the photoinitiation comprises photoinitiation under a 340-380 nm ultraviolet lamp for 1-5 min.

[0013] The second technical scheme of the present application provides the polymer adhesive based on the hydrogen bond-containing amphiphilic eutectic solvent of the acrylic derivative prepared by the preparation method.

[0014] The third technical scheme of the present application provides the application of the polymer adhesive based on the hydrogen bond-containing amphiphilic eutectic solvent of the acrylic derivative in the adhesion of hydrophilic surface materials and low-surface-energy hydrophobic materials in air and water environments, wherein the hydrophilic surface materials include glass, metal or wood; and the low-surface-energy hydrophobic materials include polytetrafluoroethylene.

[0015] The technical mechanism of the present application is as follows: The present application realizes the strong adhesion to different surface energy substrates by constructing a dynamic multi-level network structure with hydrophilic and hydrophobic properties, and maintains excellent interfacial stability and functional durability in water and complex chemical environments.

[0016] The system takes the amphiphilic eutectic solvent as the key medium, which is formed by heating and blending of specific molar ratio of amphiphilic hydrogen bond donor and hydrogen bond acceptor. The eutectic solvent not only acts as a reaction medium, but also participates in the formation of the polymer network as a structural component. The molecular structure of the eutectic solvent contains both polar groups and non-polar segments, which can guide the microphase separation of acrylate and acrylamide monomers during polymerization, forming an interpenetrating network with interlaced hydrophobic and hydrophilic domains. The hydrophobic region is mainly composed of acrylate monomers and the synergistic effect of the hydrophobic components in the eutectic solvent, which can effectively block the penetration of water molecules, inhibit the formation of interfacial hydration layer, and strongly adsorb on the surface of polytetrafluoroethylene and other low-surface-energy materials through hydrophobic interaction; the hydrophilic region provides abundant hydrogen bond sites by the polar part of the acrylamide monomer and the eutectic solvent, so that it forms a high-strength and reversible physical crosslinking with glass, metal, wood and other high-surface-energy materials.

[0017] In addition, the introduced chemical cross-linking agent forms a covalent cross-linking network by photo-induced radical polymerization, significantly improving the mechanical strength, anti-swelling property and structural integrity of the overall material, so that it can still maintain stable adhesion performance in harsh environments such as seawater, acid and alkali solutions without degradation or falling off.

[0018] The adhesive also exhibits significant recyclability and on-demand peeling ability due to the reversible reconstruction of a large number of dynamic hydrogen bonds and physical interactions in its network, which can autonomously restore the adhesion function after damage.

[0019] More prominently, the amphiphilic porous network structure provides efficient adsorption sites for volatile organic compounds (VOCs) due to its rich micro-nano pores and specific functional groups (such as hydroxyl, carboxyl, sulfonic acid groups from eutectic solvent and monomer), which realize high-capacity adsorption of various VOCs (such as ethanol, acetone, ethyl acetate, etc.) through pore capture, van der Waals force and hydrogen bonding.

[0020] The present application discloses the following technical effects: The present application introduces amphiphilic eutectic solvent (composed of amphiphilic hydrogen bond donor and hydrogen bond acceptor) into the polymer backbone network, and assists with chemical cross-linking strategy, which significantly enhances the mechanical strength of the polymer network. The hydrophobic units and hydrophobic polymer segments in the structure can effectively block the intrusion of water, repel interfacial water molecules, and avoid the destruction of the bonding interface, thereby realizing long-term stable adhesion performance in humid or underwater environments. With the hydrophobic interaction between the hydrophobic segment and the substrate, and the multiple hydrogen bond interactions provided by the hydrophilic component, the adhesive can widely adapt to different polar substrate materials, and exhibits excellent and stable adhesion to hydrophilic surface materials (such as glass, metal, wood) and low surface energy hydrophobic materials (such as polytetrafluoroethylene). In addition, the adhesive also exhibits excellent on-demand debonding ability, significantly improving its reusability and service life.

[0021] It is worth emphasizing that the amphiphilic eutectic solvent polymer adhesive has good adsorption performance for VOCs. On the one hand, the interaction between the hydrogen bond donor and the acceptor builds a rich pore structure. This pore structure is like a huge "capture network" for VOC molecules, which can efficiently adsorb VOC molecules in the air. On the other hand, the eutectic solvent and comonomer containing specific functional groups such as hydroxyl, amide, carboxyl, etc. are introduced into the adhesive by ultraviolet curing copolymerization. These functional groups can form hydrogen bonds and other forces with VOC molecules, further enhancing the adsorption performance.

[0022] In summary, the present application not only effectively solves the bottleneck problems of the existing adhesive, such as weak adhesion to low surface energy materials, insufficient adsorption performance to VOCs and performance degradation in water environment, but also provides important material basis and technical support for the development of high-end equipment manufacturing, ocean engineering and reusable intelligent bonding materials. BRIEF DESCRIPTION OF DRAWINGS

[0023] Figure 1 Adhesion diagram of the adhesive of Example 1 to different materials; Figure 2 Adhesion diagram of the adhesive of Example 2 to different materials under water; Figure 3 Cyclic use adhesion diagram of the adhesive of Example 3; Figure 4 Adhesion diagram of the adhesive of Example 4 in different environments; Figure 5 Adsorption diagram of the adhesive of Example 5 to different VOCs; Figure 6 Adhesion diagram of the adhesive of Comparative Example 1 to different materials; Figure 7 Adhesion diagram of the adhesive of Comparative Example 3 to different materials. DETAILED DESCRIPTION

[0024] Various exemplary embodiments of the present application will now be described in detail, which should be considered to be illustrative of the present application and not restrictive of the same. It should be understood that the detailed description and specific examples, while indicating certain embodiments of the application, are intended to be illustrative only and are not intended to limit the scope of the application.

[0025] It should be understood that the terms used in the present application merely describe particular embodiments and are not intended to limit the present application. In addition, for numerical ranges in the present application, it should be understood that each intermediate value between the upper limit and the lower limit of the range is also specifically disclosed. Each smaller range within any stated range or within any stated intermediate value, as well as any other stated value or intermediate value within the stated range, is also encompassed within the present application. The upper and lower limits of these smaller ranges can be independently included or excluded from the range.

[0026] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. Although methods and materials similar or equivalent to those described herein can be used in the practice or testing of the present application, preferred methods and materials are described. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials in connection with which the documents are cited. In the case of conflict between any document incorporated by reference and the present specification, the present specification will control.

[0027] Many modifications and variations of the present application described in the specification are possible without departing from the scope or spirit of the application. Other implementations of the application will be apparent to those skilled in the art from consideration of the specification and practice of the application. The specification and examples are illustrative only.

[0028] As used herein, the terms "comprises", "comprising", "includes", "including", "has", "having" and the like are open-ended terms that are intended to permit but not limit the inclusion of elements or the number of elements, as the case can be.

[0029] It should be noted that the present application does not describe in detail the conventional means of the art, and is not the focus of the present application.

[0030] The raw materials used in the following examples and comparative examples of the present application are commercially available unless otherwise specified, and the source of the commercially available products does not affect the technical effects of the present application.

[0031] The room temperature involved in the present application is 25±5°C unless otherwise specified.

[0032] Example 1 The amphiphilic hydrogen bond acceptor tetrabutylammonium chloride and the hydrogen bond donor tributyl phosphate were mixed at a molar ratio of 1:2, stirred at 80°C until clear and transparent, to obtain a deep eutectic solvent. Then 600 mg of the deep eutectic solvent was taken, and then 600 mg of N-isopropyl acrylamide and 1200 mg of isobornyl acrylate were added thereto, and after ultrasonic mixing at room temperature, 4 mg of polyethylene glycol (diol) diacrylate was added, and ultrasonic mixing was performed at room temperature. Finally, 0.02 g of benzoin dimethyl ether was added and dissolved by ultrasonic, to obtain an adhesive precursor; the adhesive precursor was irradiated with a UV lamp of 365 nm wavelength at room temperature for 3 min, to prepare a polymer adhesive.

[0033] The adhesive obtained in the present example was tested for VOCs adsorption capacity and adhesion: VOCs adsorption capacity: first, 5 mL of a test tube was weighed and recorded as m1, the prepared adhesive precursor was added to the 5 mL test tube, and the adhesive was prepared by initiating at 365 nm wavelength, the prepared adhesive test tube was weighed again and recorded as m2, m2-m1 was the original weight of the adhesive, then the prepared adhesive test tube was placed into a conical flask containing 300 mL of ethyl acetate and strictly sealed with a sealing film to prevent organic solvent evaporation. Then, the test tube was weighed every 24 h and recorded as m, so the 24 h adsorption amount was m-m2. The adsorption capacity calculation formula is (m-m2) / (m2-m1).

[0034] The adhesive obtained in the example can adsorb ethyl acetate. After 10 days of adsorption, m is 10.1219 g, the original weight of the adhesive m2-m1 is 7.2187 g-6.4924 g=0.7263 g, and thus the adsorption capacity of the adhesive is 4 g / g (i.e., each gram of the adhesive can adsorb 4 g of the adsorbate) according to the calculation formula.

[0035] Adhesion: The maximum adhesive strength of the adhesive obtained in the example at 20°C can reach 2000 kPa for hydrophilic material glass, 1549 kPa for wood, 1112.7 kPa for iron, 924.5 kPa for copper, 1540 kPa for hydrophobic material rubber shoe sole, and 1561.3 kPa for polytetrafluoroethylene plastic plate (results are shown in Table 1). Figure 1 This fully shows that the adhesive has strong adhesion to various substrates.

[0036] Example 2 The amphiphilic hydrogen bond acceptor tetrabutylammonium bromide and the hydrogen bond donor menthol were mixed at a molar ratio of 2:1, stirred at 80°C until clear and transparent, and a eutectic solvent was obtained. 500 mg of the eutectic solvent was taken, and then 400 mg of 4-hydroxybutyl acrylate and 1400 mg of tert-butyl acrylate were added thereto. After being uniformly mixed by ultrasonic treatment at room temperature, 4 mg of polyethylene glycol (diol) diacrylate was added and uniformly mixed by ultrasonic treatment at room temperature. Finally, 0.02 g of 2-hydroxy-2-methyl-1-phenylpropanone was added and dissolved by ultrasonic treatment, and an adhesive precursor was obtained. The adhesive precursor was irradiated with a UV lamp with a wavelength of 365 nm for 2 min at room temperature, and a polymer adhesive was prepared.

[0037] The adsorption capacity of the adhesive obtained in the example for VOCs and its adhesion were tested. Adsorption capacity for VOCs: First, a 5 mL test tube was weighed and recorded as m1. The prepared adhesive precursor was added to the 5 mL test tube, and the adhesive was prepared by initiating at a wavelength of 365 nm. The prepared adhesive test tube was weighed again and recorded as m2, and m2-m1 was the original weight of the adhesive. Then, the prepared adhesive test tube was placed in a conical flask containing 300 mL of ethanol and 300 mL of propanol, respectively, and was strictly sealed with a sealing film to prevent the evaporation of the organic solvent. Then, the test tube was weighed every 24 h and recorded as m, and thus the 24 h adsorption amount was m-m2. The adsorption capacity calculation formula is (m-m2) / (m2-m1).

[0038] The adhesive obtained in the embodiment can adsorb ethanol and propanol. According to the adsorption capacity calculation formula, after 10 days of adsorption, the adsorption capacity is 3.2 g / g (i.e. 3.2 g of adsorbate can be adsorbed per gram of adhesive, ethanol) and 4 g / g (i.e. 4 g of adsorbate can be adsorbed per gram of adhesive, propanol), respectively.

[0039] Adhesion: The maximum adhesive strength of the adhesive obtained in the embodiment to glass under water can reach 890.4 kPa, to wood can reach 697.7 kPa, to iron can reach 778.7 kPa, to copper can reach 869.4 kPa, to hydrophobic material rubber shoe sole can reach 835.5 kPa, and to polytetrafluoroethylene plastic plate can reach 1626.3 kPa (results are shown in Figure 2 ). This fully shows that the adhesive has strong adhesive capacity to hydrophilic and hydrophobic materials under water.

[0040] Example 3 The amphiphilic hydrogen bond acceptor n-octanoic acid and the hydrogen bond donor menthol were mixed at a molar ratio of 2:1, stirred at 80°C until clear and transparent, to obtain a eutectic solvent. 500 mg of the eutectic solvent was taken, then 600 mg of N-isopropyl acrylamide and 1200 mg of 2-hydroxyethyl methacrylate were added thereto, and after ultrasonic mixing at room temperature, 4 mg of polyethylene glycol (diol) diacrylate was added and ultrasonically mixed at room temperature. Finally, 0.02 g of 2-hydroxy-2-methyl-1-phenylpropanone was added and dissolved by ultrasonication, to obtain an adhesive precursor; the adhesive precursor was irradiated with a UV lamp of 365 nm wavelength for 2 min at room temperature, to prepare a polymer adhesive.

[0041] The obtained adhesive was used to bond rubber shoe soles, which were placed in an oven environment at 80°C for 30 min after being bonded for 24 h, and the rubber shoe soles could be easily peeled off and the bonding process was repeated according to the process. The ordinary adhesive achieves high-strength bonding through irreversible covalent curing, and the interface chemical bond is broken when peeled off and the energy cannot be dissipated again, so it is invalid and cannot be reused. The gel adhesive prepared by the method of the present application utilizes the reversible physical crosslinking of hydrogen bonds, which can quickly restore the network and interface interaction after peeling, thereby realizing the recycling of "bonding-peeling-rebonding" and maintaining strong adhesion after being used repeatedly for 6 times (results are shown in Figure 3 ).

[0042] Example 4 The amphiphilic hydrogen bond acceptor tetrabutylammonium chloride and the hydrogen bond donor tributyl phosphate were mixed in a molar ratio of 1:2, stirred at 80°C until clear and transparent, to obtain a eutectic solvent. 600 mg of the eutectic solvent was taken, then 600 mg of 4-hydroxybutyl acrylate and 1200 mg of tert-butyl acrylate were added thereto, and after being mixed uniformly at room temperature by ultrasonic mixing, 4 mg of polyethylene glycol (diol) diacrylate was added, and mixed uniformly at room temperature by ultrasonic mixing. Finally, 0.02 g of benzoin dimethyl ether was added, and dissolved by ultrasonic mixing, to obtain an adhesive precursor; the adhesive precursor was irradiated with a UV lamp of 365 nm wavelength at room temperature for 3 min, to prepare a polymer adhesive.

[0043] The adhesive obtained in this example was tested for its adsorption capacity for VOCs and its adhesion: Adsorption capacity for VOCs: first, a 5 mL test tube was weighed and recorded as m1, the prepared adhesive precursor was added to the 5 mL test tube, and the prepared adhesive was initiated at 365 nm wavelength, the prepared adhesive test tube was weighed again and recorded as m2, m2-m1 was the original weight of the adhesive, then the prepared adhesive test tube was placed into a conical flask containing 300 mL of acetone and was strictly sealed with a sealing film to prevent organic solvent evaporation. Then, the test tube was weighed every 24 h and recorded as m, so the 24 h adsorption amount was m-m2. The adsorption capacity calculation formula was (m-m2) / (m2-m1).

[0044] The adhesive obtained in this example was tested for its adsorption capacity for VOCs and its adhesion:

[0045] Adhesion: the adhesive obtained in this example was adhered to polytetrafluoroethylene, and then was immersed in water, seawater, 1 mol / L hydrochloric acid and 1 mol / L sodium hydroxide solution for 7 days, respectively, and then was taken out, and the adhesion forces were 1637.4 kPa, 1947.9 kPa, 1345.8 kPa and 1467.3 kPa, respectively, without weakening or debonding (results are shown in Figure 4

[0046] Example 5 ​The amphiphilic hydrogen bond acceptor tetrabutylammonium bromide and the hydrogen bond donor menthol were mixed at a molar ratio of 2:1, stirred at 80°C until clear and transparent to obtain the eutectic solvent 2. 600 mg of the eutectic solvent was taken, then 600 mg of 4-hydroxybutyl acrylate and 1200 mg of N-hydroxyethyl acrylamide were added thereto, and after being uniformly mixed by ultrasonic mixing at room temperature, 4 mg of polyethylene glycol (diol) diacrylate was added and uniformly mixed by ultrasonic mixing at room temperature. Finally, 0.02 g of benzoin dimethyl ether was added and dissolved by ultrasonic mixing to obtain an adhesive precursor; the adhesive precursor was irradiated with a UV lamp of 365 nm wavelength at room temperature for 3 min to prepare a polymer adhesive.

[0047] The adhesive obtained in this example was tested for its adsorption capacity for VOCs and its adhesion: Adsorption capacity for VOCs: First, a 5 mL test tube was weighed and recorded as m1, the prepared adhesive precursor was added to the 5 mL test tube, and the prepared adhesive was initiated at 365 nm to prepare the adhesive. The prepared adhesive test tube was weighed again and recorded as m2, m2-m1 was the original weight of the adhesive, then the prepared adhesive test tube was placed into a conical flask containing 300 mL of methanol, 300 mL of ethanol, and 300 mL of acetone, and was strictly sealed with a sealing film to prevent the organic solvent from evaporating. Then, the test tube was weighed every 24 h and recorded as m, so the 24 h adsorption amount was m-m2. The adsorption capacity calculation formula is (m-m2) / (m2-m1).

[0048] The adhesive obtained in this example has good adsorption capacity for various volatile organic compounds, and after 10 days of adsorption, the adsorption effect on methanol is the best, reaching 1.5 g / g (i.e. 1.5 g of adsorbate can be adsorbed per gram of adhesive) (results as shown in Figure 5

[0049] Example 6 The amphiphilic hydrogen bond acceptor lauric acid and the hydrogen bond donor thymol were mixed at a molar ratio of 2:1, stirred at 80°C until clear and transparent to obtain a eutectic solvent. 600 mg of the eutectic solvent was taken, then 600 mg of N-isopropyl acrylamide and 1200 mg of N-hydroxymethyl acrylamide were added thereto, and after being uniformly mixed by ultrasonic mixing at room temperature, 4 mg of polyethylene glycol (diol) diacrylate was added and uniformly mixed by ultrasonic mixing at room temperature. Finally, 0.02 g of benzoin dimethyl ether was added and dissolved by ultrasonic mixing to obtain an adhesive precursor; the adhesive precursor was irradiated with a UV lamp of 365 nm wavelength at room temperature for 3 min to prepare a polymer adhesive.

[0050] ​The adhesive is respectively adhered to glass, wood material, copper, iron, hydrophobic material rubber sole, and polytetrafluoroethylene plastic plate, and then the adhered material is placed in an oven at 80 ℃ for 30 min and taken out, and can be easily peeled off. When the temperature rises, the hydrogen bond / coordinating bond at the gel-substrate interface is pyrolyzed, the hydrophobic association is melted, and the chain segment relaxation is accelerated, and multiple mechanisms are cooperated, so that the interfacial free energy is converted from negative to positive, the storage modulus is suddenly reduced, and the macroscopic performance is that the adhesion force is significantly reduced and is easy to peel off.

[0051] Comparative Example 1 The hydrophilic hydrogen bond acceptor choline chloride and the hydrophilic hydrogen bond donor ethylene glycol are mixed at a molar ratio of 1:2, stirred at 80 ℃ until clear and transparent, and a eutectic solvent is obtained. 500 mg of the eutectic solvent is taken, then 400 mg of 4-hydroxybutyl acrylate and 1400 mg of tert-butyl acrylate are added, and after being uniformly mixed by ultrasonic at room temperature, 4 mg of polyethylene glycol (diol) diacrylate is added, and uniformly mixed by ultrasonic at room temperature. Finally, 0.02 g of 2-hydroxy-2-methyl-1-phenylpropanone is added and dissolved by ultrasonic, and an adhesive precursor is obtained; the adhesive precursor is irradiated with a 365 nm wavelength ultraviolet lamp at room temperature for 2 min, and a polymer adhesive is prepared.

[0052] The difference between Comparative Example 1 and Example 2 is that the eutectic solvent composed of the amphiphilic hydrogen bond acceptor and the hydrogen bond donor is not used, and when the adhesive is soaked in water, the internal hydrophilic eutectic solvent is replaced by water, water molecules penetrate into the interior of the adhesive, destroy the hydrogen bond crosslinking in the interior of the adhesive, and make the adhesive lose the interfacial adhesion. The adhesive prepared in Comparative Example 1 is bonded to different materials, and then completely immersed in deionized water for 24 h for adhesion strength test, and it is found that the adhesion strength is greatly reduced, and cannot meet the use conditions in actual life (results are shown in Figure 6 The adhesive prepared by using the eutectic solvent composed of the amphiphilic hydrogen bond acceptor and the hydrogen bond donor in the application can maintain the interfacial adhesion even after long time immersion in water.

[0053] Comparative Example 2 The amphiphilic hydrogen bond acceptor n-octanoic acid and the hydrogen bond donor menthol are mixed at a molar ratio of 2:1, stirred at 80 ℃ until clear and transparent, and a eutectic solvent is obtained. 200 mg of the eutectic solvent is taken, then 600 mg of N-isopropyl acrylamide and 1200 mg of 2-hydroxyethyl methacrylate are added, and after being uniformly mixed by ultrasonic at room temperature, 4 mg of polyethylene glycol (diol) diacrylate is added, and uniformly mixed by ultrasonic at room temperature. Finally, 0.02 g of 2-hydroxy-2-methyl-1-phenylpropanone is added and dissolved by ultrasonic, and irradiated with a 365 nm wavelength ultraviolet lamp at room temperature for 2 min, and a polymer adhesive is prepared.

[0054] The difference between Comparative Example 2 and Example 3 is that the amount of the eutectic solvent is less than the minimum amount required in the present application, resulting in significant degradation of hydrogen bond crosslinking density, segment flowability, and cycle adhesion performance, and the adhesion strength of the rubber shoe sole after 6 cycles is 431.7 kPa, which is less than 60% of the adhesion strength retention compared with Example 3, so the amount needs to be controlled within the range required in the scheme to obtain the best adhesion-re-adhesion balance.

[0055] Comparative Example 3 The amphiphilic hydrogen bond acceptor tetrabutylammonium chloride and the hydrogen bond donor tributyl phosphate were mixed at a molar ratio of 1:2, stirred at 80°C until clear and transparent, and a eutectic solvent was obtained. 600 mg of the eutectic solvent was taken, then 600 mg of N-isopropyl acrylamide and 1200 mg of isobornyl acrylate were added, and after ultrasonic mixing at room temperature, 15 mg of polyethylene glycol (diol) diacrylate was added, and ultrasonic mixing was performed at room temperature. Finally, 0.02 g of benzoin dimethyl ether was added and dissolved by ultrasonic, and irradiated with a 365 nm wavelength ultraviolet lamp at room temperature for 3 min, to prepare a polymer adhesive.

[0056] The difference between Comparative Example 3 and Example 1 is that the amount of the crosslinking agent is greater than the maximum amount required in the present application. When the amount of the crosslinking agent is too high, the DES-gel network is excessively rigid, resulting in insufficient interfacial wetting and stress concentration, which results in adhesion strength to various materials being less than 100 kPa, which cannot meet the needs of practical applications (results shown in Figure 7

[0057] Therefore, the present application provides a preparation method of a polymer adhesive based on an acrylate derivative containing a hydrogen bond-based amphiphilic eutectic solvent with broad-spectrum adhesion. The polymer adhesive prepared by the present application not only has strong adhesion performance in underwater environments, but also maintains strong adhesion performance in various liquid environments, and also achieves broad-spectrum strong adhesion to hydrophilic / hydrophobic materials and has the excellent property of high-efficiency absorption of VOCs.

[0058] The various embodiments in the specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referred to each other.

[0059] The above description of the disclosed embodiments enables a person skilled in the art to implement or use the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.​

Claims

1. A method for preparing a broad-spectrum adhesive based on an acrylic acid derivative, a hydrogen-bonded amphiphilic eutectic solvent, characterized in that, Includes the following steps: S1. Mix the hydrogen bond donor and the hydrogen bond acceptor, heat and stir until clear to obtain a eutectic solvent; S2. Add acrylate monomers and acrylamide monomers to the eutectic solvent and mix thoroughly to obtain a mixture; S3. Add a chemical crosslinking agent and a photoinitiator to the mixture in sequence to perform photoinitiation and obtain the polymer adhesive.

2. The preparation method according to claim 1, characterized in that, The hydrogen bond donors include triethyl phosphate, tributyl phosphate, menthol, thymol, thymol, borneol, n-butanol, n-hexanol, ethylparaben, ibuprofen, p-hydroxybenzoic acid, or camphor; the hydrogen bond acceptors include tetrabutylammonium bromide, tetrabutylammonium chloride, tetrabutylhexafluorophosphate, n-butyric acid, n-valeric acid, n-hexanoic acid, n-heptanoic acid, n-octanoic acid, decanoic acid, or lauric acid; the molar ratio of the hydrogen bond donors to the hydrogen bond acceptors is 4:1 to 1:

4.

3. The preparation method according to claim 1, characterized in that, The heating temperature is 50~120℃.

4. The preparation method according to claim 1, characterized in that, The acrylate monomers include methyl acrylate, ethyl acrylate, butyl acrylate, 2-hydroxyethyl methacrylate, benzyl acrylate, isobornyl acrylate, 4-hydroxybutyl acrylate, 2,2,3,4,4,4-hexafluorobutyl acrylate, 2,2,2-trifluoroethyl acrylate, trifluoroethyl methacrylate, or tert-butyl acrylate.

5. The preparation method according to claim 1, characterized in that, The acrylamide monomers include acrylamide, N-isopropylacrylamide, N-hydroxyethylacrylamide, N-hydroxymethylacrylamide, 2-acrylamido-2-methylpropanesulfonic acid, or methacrylamide.

6. The preparation method according to claim 1, characterized in that, The chemical crosslinking agent includes N,N-methylenebisacrylamide, divinylbenzene, or polyethylene glycol (diol) diacrylate; and / or, the photoinitiator includes 2-hydroxy-2-methyl-1-phenylpropanone, 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone, benzoin dimethyl ether, or 2,4-dihydroxybenzophenone.

7. The preparation method according to claim 1, characterized in that, The mass ratio of the eutectic solvent, acrylate monomers, acrylamide monomers, chemical crosslinking agent and photoinitiator is (300~600):(300~800):(600~1600):(2~10):(10~30).

8. The preparation method according to claim 1, characterized in that, The photoinitiation includes photoinitiation under a 340-380nm ultraviolet lamp for 1-5 minutes.

9. The polymer adhesive based on acrylic acid derivatives, containing hydrogen bonds, and capable of broad-spectrum adhesion to amphiphilic eutectic solvents, prepared by the preparation method according to any one of claims 1 to 8.

10. The application of the polymer adhesive based on acrylic acid derivatives, containing hydrogen bonds, an amphiphilic low-eutectic solvent, and capable of broad-spectrum adhesion, as described in claim 9, in the adhesion of hydrophilic surface materials and low surface energy hydrophobic materials in air and water environments, characterized in that... The hydrophilic surface material includes glass, metal, or wood; and / or, the low surface energy hydrophobic material includes polytetrafluoroethylene.

Citation Information

Cited By

  • Nano-composite ionic gel material with impact resistance and preparation method of nano-composite ionic gel material

    CN121758672A